2009
DOI: 10.1111/j.1479-8298.2009.00324.x
|View full text |Cite
|
Sign up to set email alerts
|

Monthly changes in various drone characteristics of Apis mellifera ligustica and Apis mellifera syriaca

Abstract: This study was conducted to investigate drone rearing activity and semen production of Apis mellifera ligustica and Apis mellifera syriaca. Tendency of worker bees of both subspecies towards egg laying under semiarid conditions were also monitored in the experiments. Differences were not observed in drone brood production between both honeybee subspecies throughout the investigation. Worker bees of both subspecies needed a significantly shorter time to start egg laying during February and March in comparison w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 29 publications
(32 reference statements)
1
12
0
Order By: Relevance
“…Most importantly, they found that 87.8 ± 6.2% of the 35-day-old drones sampled released at least 0.2 μL of semen after manual eversion of the endophallus compared to the proportion of 14day-old drones that released at least the same volume (63.5 ± 8.5%). Likewise, Zaitoun et al (2009) found that drones of the Italian bee Apis mellifera ligustica produced more sperm (12.2 × 10 6 and 10.6 × 10 6 sperm cells, respectively) and were heavier in weight than those of the Syrian bee Apis mellifera syriaca (232 and 197 mg, respectively) in May compared to any other month (data not provided) between February and August for two consecutive years.…”
Section: Reproductive Behaviormentioning
confidence: 94%
See 2 more Smart Citations
“…Most importantly, they found that 87.8 ± 6.2% of the 35-day-old drones sampled released at least 0.2 μL of semen after manual eversion of the endophallus compared to the proportion of 14day-old drones that released at least the same volume (63.5 ± 8.5%). Likewise, Zaitoun et al (2009) found that drones of the Italian bee Apis mellifera ligustica produced more sperm (12.2 × 10 6 and 10.6 × 10 6 sperm cells, respectively) and were heavier in weight than those of the Syrian bee Apis mellifera syriaca (232 and 197 mg, respectively) in May compared to any other month (data not provided) between February and August for two consecutive years.…”
Section: Reproductive Behaviormentioning
confidence: 94%
“…In conclusion, there appears to be an overall negative effect of age on drone sperm viability (Woyke and Jasiński 1978;Locke and Peng 1993;Cobey 2007;Rhodes et al 2011;Czekońska et al 2013a) and seminal volume (Woyke and Jasiński 1978;Rhodes et al 2011;Czekońska et al 2013a;Stürup et al 2013), but these patterns are not always consistent (Czekońska et al 2013a;Metz and Tarpy 2019). Variable outcomes are also observed depending on the season (Rhodes et al 2011; as well as the genetic lines of the colonies examined (Zaitoun et al 2009;Rhodes et al 2011;Taha and Alqarni 2013). Nonetheless, despite the influence of genetics, environmental factors may exert a greater influence on sperm viability, even among drones of similar genetic origins and geographical distribution (Kumar and Kaur 2003;.…”
Section: Reproductive Behaviormentioning
confidence: 95%
See 1 more Smart Citation
“…Studies on worker development cannot be used to predict drone development because drones have different protein and carbohydrate requirements as larvae than workers . Plus drones' reproductive quality can differ not only due to differences in their body size (Berg et al, 1997;Couvillon et al, 2010), which is mainly affected by the size of cells they were reared in (Berg, 1991;Berg et al, 1997;Schlüns et al, 2003), but also depend on environmental and genetic factors (Gençer & Firatli, 2005;Zaitoun et al, 2009;Taha & Alqarni, 2013). Nutritional shortage can also affect the developmental stability of offspring and consequently their body symmetry (Ohlsson & Smith, 2001;Grønkjaer & Sand, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Drone body weight is positively associated with reproductive potential. Heavier drones have greater sperm production, fewer sperm abnormalities, and show increased representation of spermatozoa in a queen's spermatheca (Schlüns et al, 2003;Gencer and Firatli, 2005;Zaitoun et al, 2009). Thorax weight, and particularly the thorax-to-body weight ratio, reflects flight muscle development (Harrison, 1986;Marden, 1989;Coelho, 1991).…”
Section: Introductionmentioning
confidence: 99%